Characteristics of child development in the context of serious illness: a scoping review - Anne van Driessche; Leonie La Rondelle; Paul A. Boelen; Julie Brunetta; Marijke C. Kars; Mariken Spuij; Sanne L. Nijhof; Jurrianne C. Fahner (BMC Palliative Care)
Abstract Background Despite evidence on the benefits for including children in their own (palliative) care, studies show that children are not sufficiently involved nor are their preferences sufficiently elicited in a developmentally appropriate manner. The aim of this scoping review is to provide an overview of characteristics of child development in the context of serious illness. Methods A scoping review was performed using methods from Arksey and O’Malley and the Joanna Briggs Institute. A structured literature search was conducted in four databases: Medline, Embase, Psychinfo and CINAHL. Articles were included until October 2022. Thematic analysis was performed to present domains and key factors influencing child development. Results We selected 24 out of 11,246 articles. We found different characteristics describing the ongoing development of seriously ill children in early to middle childhood, early adolescence, and middle to late adolescence. Key themes were: psychological/emotional aspects, general cognitive aspects, social aspects, coping strategy, conceptualization of illness, conceptualization of death, and communication about their illness. Several accelerators of ongoing development were found (e.g. cortical maturation, prior medical experience, social experience with adults) and several decelerators (e.g. stress, hospital admission, avoidance of illness-related communication in the family). Conclusion Our review highlights essential aspects to consider when discussing illness and healthcare preferences with children at various developmental stages. However, our findings also underscore a significant gap in understanding the factors that impact the development of children with a serious illness. It is recommended to monitor development throughout the illness trajectory to gather more evidence and utilize this information to support the child’s engagement in their own healthcare in a developmentally appropriate way.